2020
DOI: 10.1016/j.jcmgh.2020.01.005
|View full text |Cite
|
Sign up to set email alerts
|

ATF2 and ATF7 Are Critical Mediators of Intestinal Epithelial Repair

Abstract: We show that ATF2 and ATF7 are dispensable for homeostatic turnover of the intestinal epithelium but are critically required to sustain sufficient epithelial repair after damage. ATF2 and ATF7 couple surface epithelial loss to a proportionate proliferative response and a decrease in secretory goblet cells providing an epithelial protective layer. BACKGROUND & AIMS: Activation factor-1 transcription factor family members activating transcription factors 2 and 7 (ATF2 and ATF7) have highly redundant functions ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…S9. This is consistent with reduced IL-22 signaling (75) and altered goblet cell development (79)). In addition, STAT6, a key regulator of secretory lineage differentiation, was predicted to have lower activity in OLFM4 expressing stem cells and immature enterocytes (80).…”
Section: Us Cohortssupporting
confidence: 68%
“…S9. This is consistent with reduced IL-22 signaling (75) and altered goblet cell development (79)). In addition, STAT6, a key regulator of secretory lineage differentiation, was predicted to have lower activity in OLFM4 expressing stem cells and immature enterocytes (80).…”
Section: Us Cohortssupporting
confidence: 68%
“…While previous work on PSMB8 has produced minimal data in relation to Toxoplasma infection ( Agarwal et al., 2010 ), further research specifically relating to chronic infection could elaborate on anti-parasitic functions in the CNS. In addition to regulating TNFα production, ATF2 is a cAMP- or activator protein-dependent transcription factor that regulates the transcription of various genes involved in anti-apoptosis, cell growth, and DNA damage response ( Falvo et al., 2000 ; Tsytsykova and Goldfeld, 2002 ; Watson et al., 2017 ; Meijer et al., 2020 ). While the effect of T. gondii infection on the transcription of TNFα has been studied in the past, the specific role of ATF2 in the context of chronic T. gondii infection in the CNS has not been elucidated, and this gene may play a vital role in regulating TNFα production specifically in the brain or by CNS-resident cells ( Leng et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to participating in inflammation-related pathological processes, a recent study reported that ATF2 and ATF7 are essential for epithelial homeostasis, but in the process of intestinal epithelial injury and repair, they need to maintain epithelial regeneration and prevent cell death. 69 …”
Section: Atf2mentioning
confidence: 99%